1996
DOI: 10.1002/(sici)1096-9861(19961111)375:2<252::aid-cne6>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Maturational gradients in the retina of the ferret

Abstract: In the present set of studies, we have examined the site for the initiation of retinal maturation in the ferret. A variety of maturational features across the developing inner and outer retina were examined by using standard immunohistochemical, carbocyanine dye labelling, and Nissl-staining techniques, including 1) two indices of early differentiation of the first-born retinal ganglion cells, the presence of beta-tubulin and of neuron-specific enolase; 2) the receding distribution of chondroitin sulfate prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 92 publications
(129 reference statements)
6
24
1
Order By: Relevance
“…Thus, differentiation starts in a region dorsal to the optic nerve head (DC region) and then progresses to the peripheral retina (unpublished observations). Similar patterns have been observed in other vertebrates (Straznicky and Gaze 1971;Prada et al 1991;Reese et al 1996;Marcus et al 1999). The possibility of a relationship between cell death and cell differentiation in the turtle retina must therefore be taken into account, and would merit investigation…”
Section: Spatial and Temporal Evolution Of Cell Deathsupporting
confidence: 65%
“…Thus, differentiation starts in a region dorsal to the optic nerve head (DC region) and then progresses to the peripheral retina (unpublished observations). Similar patterns have been observed in other vertebrates (Straznicky and Gaze 1971;Prada et al 1991;Reese et al 1996;Marcus et al 1999). The possibility of a relationship between cell death and cell differentiation in the turtle retina must therefore be taken into account, and would merit investigation…”
Section: Spatial and Temporal Evolution Of Cell Deathsupporting
confidence: 65%
“…In the Senegalese sole retina, a central‐to‐peripheral sweep of histogenesis and cell differentiation was evident. Thus, the emergence of the plexiform layers, the detection of the first postmitotic cells, and the appearance of the cell neurochemical markers started in the central retina spreading to more peripheral regions, as has been described for other teleosts (Johns and Easter, '77; Sharma and Ungar, '80; Vecino et al, '93; Hagedorn et al, '98; Vecino, '98; Doldan et al, '99; Hu and Easter, '99; Schmitt and Dowling, '99; Peterson et al, 2001; Candal et al, 2005a, 2008; Kitambi and Malicki, 2008; Bejarano‐Escobar et al, 2009) and other vertebrates (Young, '85; Prada et al, '91; Snow and Robson, '95; Reese et al, '96; Francisco‐Morcillo et al, 2005, 2006). Additionally, we found that the expression of different markers, such as Isl1 and CR, follows a vitreal‐to‐scleral gradient of appearance, as has been described for the developmental expression of CR in the brown trout (Vecino et al, '93; Candal et al, 2005b) and turbot retina (Doldán et al, '99).…”
Section: Discussionmentioning
confidence: 54%
“…Peripheral regions of the retina show expression patterns similar to central ones (data not shown). Nevertheless, a maturational delay of around 10 to 15 days has been reported for extreme peripheral parts of the ferret retina [35]. Dorsoventral differences of ganglion cell distribution have also been reported [36].…”
Section: Resultsmentioning
confidence: 99%